Carving the Clock at Its Component Joints: Neural Bases for Interval Timing - Wencil, Elaine B. (American Physiological Society, 2010)
Models of time perception often describe an “internal clock” that involves at least two components: an accumulator and a comparator. We used functional magnetic resonance imaging to test the hypothesis that distinct distributed neural networks mediate these components of time perception. Subjects performed a temporal discrimination task that began with a visual stimulus (S1) that varied parametrically in duration of presentation. A varying interstimulus interval was followed by a second visual stimulus (S2). After the S2 offset, the subject indicated whether S2 was longer or shorter than S1. We reasoned that neural activity that correlated with S1 duration would represent accumulator networks. We also reasoned that neural activity that correlated with the difficulty of comparisons for each paired-judgment would represent comparator networks. Using anatomically defined regions of interest, we found duration of S1 significantly correlated with left inferior frontal, supplementary motor area (SMA) and superior temporal regions. Furthermore, task difficulty correlated with activity within bilateral inferior frontal gyri. Therefore accumulator and comparator functioning of the internal clock are mediated by distinct as well as partially overlapping neural regions.